The Role of the Intraoperative Auxiliary Methods in the Resection of Motor Area Lesions - Sarmento, Stênio Abrantes; Andrade, Emerson Magno de; Tedeschi, Helder (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2015)
Objective In recent years, technologies have advanced considerably in improving surgical outcome following treatment of lesions in eloquent brain areas. The aim of this study is to explore which method is best in the resection of motor area lesions. Methods Prospective, non-randomized study Evaluate on 74 patients who underwent surgery to remove lesions around the motor area.Results Total lesion removal was achieved in 68 patients (93.1%). Fifty-four patients (73.9%) presented normal motor function in the preoperative period; of these, 20 (37.3%) developed transitory deficits. Nevertheless, 85% of these patients later experienced a complete recovery. Nineteen patients presented with motor deficits preoperatively; of these, five presented deteriorating motor abilities. Intraoperative stimulation methods were used in 65% of the patients, primarily in cases of glioma. Conclusions The morbidity in patients submitted to resections of motor area lesions is acceptable and justify the surgical indication with the purpose of maximal resection. Intraoperative stimulation is an important tool that guides glioma resection in many cases.
Keywords: motor cortex; brain neoplasms; stereotaxic techniques; neuronavigation